2007
DOI: 10.1016/j.im.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Post-adoption behavior of users of Internet Service Providers

Abstract: This study examines post-adoption behavior in the Internet

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…In this study, data on intention is collected rather than actual usage of technology. There are a number of reasons for this: (1) access to information on the use of technology in schools is sensitive; (2) asking teachers to report their actual use (e.g., number of hours or number of lessons in the computer lab) may result in socially-desirable data, that is, a situation where participants respond in what they perceive is a desired way by reporting a higher level of technology use; (3) intention has been viewed as being more progressive and predictive compared to actual use, which is more static and retrospective (e.g., Roca et al 2006;Spiller et al 2007), and (4) Intention is an indication of an individual's readiness to perform a given behavior, and is considered to be the immediate antecedent of behavior and there is a strong correlation between intention and actual usage (Ajzen 2005;Fishbein and Ajzen 1975).…”
Section: Research Model and Hypotheses Behavioral Intention (Bi)mentioning
confidence: 99%
“…In this study, data on intention is collected rather than actual usage of technology. There are a number of reasons for this: (1) access to information on the use of technology in schools is sensitive; (2) asking teachers to report their actual use (e.g., number of hours or number of lessons in the computer lab) may result in socially-desirable data, that is, a situation where participants respond in what they perceive is a desired way by reporting a higher level of technology use; (3) intention has been viewed as being more progressive and predictive compared to actual use, which is more static and retrospective (e.g., Roca et al 2006;Spiller et al 2007), and (4) Intention is an indication of an individual's readiness to perform a given behavior, and is considered to be the immediate antecedent of behavior and there is a strong correlation between intention and actual usage (Ajzen 2005;Fishbein and Ajzen 1975).…”
Section: Research Model and Hypotheses Behavioral Intention (Bi)mentioning
confidence: 99%
“…While such sites are valuable, their success depends on the continuous use of these sites (Brazelton & Gorry, 2003;Chen, 2007;Parthasarathy & Bhattacherjee, 1998;Spiller et al, 2007;Tiwana & Bush, 2005). Without sustaining the use, such sites would lose their memberships and as a result fail to achieve their advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Without sustaining the use, such sites would lose their memberships and as a result fail to achieve their advantages. Further, recruiting a new member requires about six times higher cost than maintaining an existing members in paid online services, given the cost of marketing and setting up new members (Spiller et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…According to the 'Information Technology (IT) Spending Forecast' published by Gartner (2014), worldwide dollar-valued IT spending will grow 3.2 % in 2014, reaching USD 3.8 trillion. The existing research has demonstrated that it costs approximately six times as much to recruit a new subscriber as it does to maintain an old one in paid membership contexts (Spiller, Vlasic, & Yetton, 2007). For example, in the case of Internet service providers (ISPs), an extra 1 % retention can add as much as 5 % to the bottom line of the business (Vatanasombut, Igbaria, Stylianou, & Rodgers, 2008).…”
mentioning
confidence: 99%